THE PRACTICES OF INTENTIONAL VOCABULARY ACQUISITION FOR ASIAN EFL LEARNERS: A SYSTEMATIC REVIEW - Peggy Magdalena Jonathans; Utami Widiati; Indri Astutik; Devinta Puspita Ratri (University of Kuningan, 2021)
This systematic literature review attempts to shed light on the practice of vocabulary acquisition in EFL contexts (incidental versus intentional mode) and the recommendation for Asia. Aiming to fill theoritical gap, the present study elucidates methodological-related variables dealing with vocabulary acquisition Asia EFL teaching mostly needed and relevantly applicable. The study serves as a call for Asia EFL teachers to elaborate all reviewed components into ELT practice and curriculum. PRISMA is applied for the study methodology while inclusion criterion used to key terms in search engines which found 13,653 articles, and resulted into 27 the most related studies within the 15-year-time frame after being circumscribed, comprising publication on incidental and intentional vocabulary acquisition. The findings from the analysis indicated that extensive reading as the main input with additional of other skills. Exposure and repetition for meanings and retentions should be balancedly planned preventing from counterproductive effects. The explicit instruction needs of integration of interrelated components for the acquisition and learning to occur, namely input, media, time length, meanings, tasks, EFL teachers roles, L2 learners motivation, references, and evaluation. The larger the vocabulary size, the greater their engagement in L2 learning and real communication. The pedagogical implication recommends strongly intentional vocabulary acquisition with intentional vocabulary mode as supplementary since the two modes codeswitch in the cognitive domain.